The Agile Organization: How to Build an Engaged, Innovative and Resilient Business - Linda Holbeche (UK Kogan Page, 2018)
In today's volatile and ambiguous world, organizations need to have the capacity and flexibility to respond rapidly to changes in their environment, both internally and externally. The key to retaining competitive advantage is agility, a set of capabilities that help organizations adapt with the full co-operation of their employees. The Agile Organization is a practical blueprint to building both agility and resilience at individual, team and organizational levels. It draws on case studies such as ING, the UK National Health Service, the Royal Bank of Scotland (RBS) and Atkins, as well as on the lived experience of HR and organization development (OD) professionals, to show how it is possible to build a sustainably agile business while enhancing employee engagement and resilience. This revised 2nd edition of The Agile Organization showcases new organizational models, ground-breaking themes and case studies which illustrate how organizations are addressing the challenge of developing organizational agility. Packed with helpful checklists, self-assessment tools, guidelines and new material on agile strategizing, people, environments and cultures, this book remains a 'go to guide' for HR and OD specialists, senior leaders and managers who want to help bring about organizational transformation.
Keywords: Organizational change; Organizational behavior; Organizational effectiveness; Personnel management; Corporate culture; Management; Agile Management (HRM2072-N)